Bottom-Up Abstract Modelling of Optical Networks-on-Chip: From Physical to Architectural Layer - Alberto Parini; Luca Ramini; Fabio Lanzoni; Gaetano Bellanca; Davide Bertozzi (International Journal of Optics)
This work presents a bottom-up abstraction procedure based on the design-flow FDTD + SystemC suitable for the modelling of optical Networks-on-Chip. In this procedure, a complex network is decomposed into elementary switching elements whose input-output behavior is described by means of scattering parameters models. The parameters of each elementary block are then determined through 2D-FDTD simulation, and the resulting analytical models are exported within functional blocks in SystemC environment. The inherent modularity and scalability of the S-matrix formalism are preserved inside SystemC, thus allowing the incremental composition and successive characterization of complex topologies typically out of reach for full-vectorial electromagnetic simulators. The consistency of the outlined approach is verified, in the first instance, by performing a SystemC analysis of a four-input, four-output ports switch and making a comparison with the results of 2D-FDTD simulations of the same device. Finally, a further complex network encompassing 160 microrings is investigated, the losses over each routing path are calculated, and the minimum amount of power needed to guarantee an assigned BER is determined. This work is a basic step in the direction of an automatic technology-aware network-level simulation framework capable of assembling complex optical switching fabrics, while at the same time assessing the practical feasibility and effectiveness at the physical/technological level.